2014
DOI: 10.17511/ijmrr.2014.i04.10
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mechanical Ventilation-Early Experiences in central India

Abstract: Introduction: This innovative technology of mechanical ventilation had been started since 1960s and reached to significant level in affluent nation but in our nation, it is in nascent stage. This is first kind of study measuring outcome of neonatal mechanical ventilation in central part of India. . Out of total 1160 admission during study period over one year in our NICU, 79 newborns (6.81%) requiring mechanical ventilation were enrolled. 70 (88.60%) newborn were given SIMV mode and 9 (11.40%) were given exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
4
9
0
Order By: Relevance
“…[ 6 ] In the present study, the most ventilated babies were 0f 1000–1499 g (18%) while the mean birth weight in survived neonates was 2173 ± 665 g and expired neonates was 1611 ± 792 g. Trivedi et al .,[ 7 ] Hossain et al .,[ 5 ] and Dutt et al . [ 2 ] also reported higher survival in babies weighing >2000 g: 56.7%, 52.1%, and 51%, respectively, as in our study, it was 52.6%. The intrauterine growth showed statistical significance ( P < 0.01) showing that AGA babies had the highest survival rate (54.5%) and mortality was least in LGA babies.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…[ 6 ] In the present study, the most ventilated babies were 0f 1000–1499 g (18%) while the mean birth weight in survived neonates was 2173 ± 665 g and expired neonates was 1611 ± 792 g. Trivedi et al .,[ 7 ] Hossain et al .,[ 5 ] and Dutt et al . [ 2 ] also reported higher survival in babies weighing >2000 g: 56.7%, 52.1%, and 51%, respectively, as in our study, it was 52.6%. The intrauterine growth showed statistical significance ( P < 0.01) showing that AGA babies had the highest survival rate (54.5%) and mortality was least in LGA babies.…”
Section: Discussionsupporting
confidence: 85%
“…Dutt et al . [ 2 ] found it as the third-most common (18.98%) while Mathur et al . [ 3 ] as fourth-most common cause (8.4%) of ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other Indian studies reported a similar cohort with 16 to 17% for < 32 weeks gestation, 30% to 40% for 32 to 37 respectively. 10,11 Preterm babies suffer from RDS, apnea, sepsis, pneumonia, pulmonary haemorrhage etc. and they need mechanical ventilation more than term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…MV (Mechanical Ventilation) was introduced in the West in 1960s to support the infants with respiratory failure 11 . This innovative technology have reached to significant level in affluent nation, but due to its high cost, expert skill requirements has limited its use in developing countries 12 . Bangladesh is a developing country.…”
Section: Original Articlementioning
confidence: 99%